Midwives' perceptions of being 'with woman': A phenomenological study - Bradfield, Zoe; Hauck, Yvonne; Duggan, Ravani; Kelly, Michelle (BMC, 2019)
© 2019 The Author(s). Background: Being 'with woman' is a central construct of the midwifery profession however, minimal research has been undertaken to explore the phenomenon from the perspective of midwives. The aim of this study was to describe Western Australian midwives' perceptions of the phenomenon of being 'with woman' during the intrapartum period. Methods: Descriptive phenomenology was selected as the methodology for this study. Thirty one midwives working across a variety of care models participated in individual interviews. Giorgi's four stage phenomenological approach was employed to analyse data. Results: Three themes were extracted 1) Essential to professional identity; 2) Partnership with women; and 3) Woman-Centred Practice. Midwives described the importance of being 'with woman' to the work and identification of midwifery practice. Developing a connection with the woman and providing woman-centred care inclusive of the woman's support people was highlighted. Conclusions: For the first time, we are able to offer evidence of how midwives understand and perceive the phenomenon of being 'with woman' which has theoretical and practical utility. Findings from this study provide evidence that supports expert commentary and confirms that midwives conceptualise the phenomenon of being 'with woman' as essential to the identity and practice of the profession. Some previously identified 'good midwifery practices' were revealed as practical manifestations of the phenomenon. This new knowledge facilitates clarity and provides evidence to support statements of professional identity, which is useful for the development of educational curricula as well as supporting graduate and professional midwives. The findings emphasise the importance of the development of language around this important philosophical construct which permeates midwifery practice, enhances professional agency and supports the continued emphasis of being 'with woman' with new understanding of its applied practices in a variety of care models.